2020
DOI: 10.21203/rs.3.rs-24052/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A five year trend analysis of malaria prevalence in Guba district, Benishangul-Gumuz Regional State, western Ethiopia: A retrospective study

Abstract: Background: In Ethiopia, malaria is a serious public health concern and has great impact on socio-economy. The trend analysis of malaria data from health facilities is useful for understanding its transmission dynamics and implementing evidence-based malaria control strategies. The aim of this study was to determine the trends of malaria infection in Guba district, western Ethiopia. Methods: A retrospective study was undertaken at Mankush Health Centre, western Ethiopia. All malaria cases reported from 2014 to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
6
5
1
Order By: Relevance
“…The present study had observed higher prevalence of malaria among age group of 15-24 years old than younger children and older adults which is in line with studies done in other parts of Ethiopia[6,11,25]. This might be due to the fact that productive age groups frequently engaged in outdoor activities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study had observed higher prevalence of malaria among age group of 15-24 years old than younger children and older adults which is in line with studies done in other parts of Ethiopia[6,11,25]. This might be due to the fact that productive age groups frequently engaged in outdoor activities.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of that, the peak in malaria cases occurred in July followed by November which is harvesting season during and after the main rainfall. The highest cases of malaria were detected during autumn (September-November) which was in consistent with the ndings of the studies carried out in Dembia [6], Dembecha [17], Northwest Tigray [4], Ataye [25], Guba [11], Jimma [41], and Harari [20]. It might be due to the heavy rains creating suitable environment for the breading of Anopheles mosquitoes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, Deribew and his colleagues have also documented the decrement of malaria new cases and deaths from 2.8 million to 621,345 cases, and 30,323.9 to 1561.7 deaths in 1990 and 2015, respectively [12]. A previous retrospective studies have also reported malaria reduction [13][14][15]. However, the report on decline of malaria is not conclusive that public health emergency management (PHEM) has shown an increased malaria transmission [11], and have no clearly de ned situation of malaria [10].…”
Section: Introductionmentioning
confidence: 99%